(untitled) (Contemporary Journal of Social Science Review, 2025)
Psychological well-being is an essential marker of the positive mental health of children and adolescents. In order to measure this phenomenon appropriately across diverse cultures, native language measures are needed. Therefore, this study aimed to validate an Urdu version (BSPWB-U) of the Brief Psychological Well-being Scale for Adolescents (BSPWB-A; Viejo et al., 2018) on a sample of 561 adolescent boys aged 14 to 18 years (M=15.00, SD=0.93) in Lahore, Pakistan. The BSPWB-A was administered in Urdu after forward and backward translation of the 20-item English version. The Self-Esteem Scale for Children (SESC; Saleem & Mahmood, 2011) was also administered to determine the adapted scale’s convergent and discriminant validity. Confirmatory factor analyses confirmed the original four-factor structure for the BSPWB-U, and the scale showed satisfactory reliability along with convergent and discriminant validity with SESC. The BSPWB-U is a comprehensive yet brief measure to assess the psychological well-being of Urdu-speaking adolescent boys in Pakistan and diasporic communities in multicultural societies worldwide. However, a validation of the measure with girls or with gender-balanced samples is needed to assess its appropriateness with Urdu-speaking girls.